2005
DOI: 10.1111/j.1365-2826.2005.01297.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Immediate Early Genes and Vasopressin Heteronuclear RNA in the Paraventricular and Supraoptic Nuclei of Rats After Acute Osmotic Stimulus

Abstract: Monitoring the expression of immediate early genes (IEGs) is useful for following stress-induced cellular responses in the neuroendocrine system. We have examined the transcriptional activities of four IEGs (c-fos, junB, NGFI-A and NGFI-B) and of the arginine vasopressin (AVP) gene in the hypothalamic paraventicular (PVN) and supraoptic nuclei (SON) of rats after acute osmotic stimuli, using in situ hybridization histochemistry. After intraperitoneal (i.p.) administration of hypertonic saline (2% body weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 49 publications
5
49
1
Order By: Relevance
“…shown to be upregulated in the SON after dehydration (Carter and Murphy, 1990;Sharp et al, 1991;Luckman et al, 1996;Miyata et al, 2001b;Cunningham et al, 2004;Ji et al, 2005;Kawasaki et al, 2005;Penny et al, 2005;Gottlieb et al, 2006). Here we identify JunD as also being upregulated (supplemental Table 3, available at www.jneurosci.org as supplemental material), an observation that we confirmed by in situ hybridization and immunocytochemistry (Yao et al, unpublished observation).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…shown to be upregulated in the SON after dehydration (Carter and Murphy, 1990;Sharp et al, 1991;Luckman et al, 1996;Miyata et al, 2001b;Cunningham et al, 2004;Ji et al, 2005;Kawasaki et al, 2005;Penny et al, 2005;Gottlieb et al, 2006). Here we identify JunD as also being upregulated (supplemental Table 3, available at www.jneurosci.org as supplemental material), an observation that we confirmed by in situ hybridization and immunocytochemistry (Yao et al, unpublished observation).…”
Section: Discussionsupporting
confidence: 74%
“…Effect of water deprivation on the distribution of cells expressing Atf4, Cebpb, Creb3l1, Giot1, and Giot2␤ in the SON and PVN of the control (C) and dehydrated (D been shown to be induced by cAMP intracellular signaling pathways through a CRE (Yazawa et al, 2003). Furthermore, the Giot1 promoter has been shown recently to be a target of the orphan nuclear receptor Nr4a1 (nuclear receptor subfamily 4, group A, member 1) (also known as Nur77 or NGFIB) (Song et al, 2006) transcription factor, which is also upregulated in the SON after dehydration (supplemental Table 3, available at www.jneurosci.org as supplemental material) (Luckman, 1997;Kawasaki et al, 2005). Nr4a1 is also known to be under the control of cAMP pathways (Humphries et al, 2004).…”
Section: Atf4mentioning
confidence: 99%
“…Detection of a change in SI in a hypothalamic region may therefore reflect a change in neuronal activity at that time point, or it may correspond to the earliest time point at which a change in neuronal activity becomes detectable, once sufficient Mn 2ϩ ions have penetrated into that region. Peripheral injection of hypertonic NaCl strongly induces FLI in the SON and PVN (Han and Rowland, 1996;Xiong and Hatton, 1996;Kawasaki et al, 2005). The SON is anatomically more distant from the ME than the Arc, and this is reflected in the relatively slow rate of rise in SI over the 2 h of each scan.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence has demonstrated that the expression level and release of AVP are both significantly increased by osmotic stimulation [8,24,25]. Recently, it has also been reported that GFP signals in the hypothalamus and posterior pituitary of AVP-eGFP Tg rats are considerably amplified by saltloading [9].…”
Section: Discussionmentioning
confidence: 96%